The gigA/gigB Genes Regulate the Growth, Stress Response, and Virulence of Acinetobacter baumannii ATCC 17978 Strain - Zhou, Hua; Gebhardt, Michael J.; Czyz, Daniel M.; Yao, Yake; Shuman, Howard A. (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is an important pathogen of nosocomial infection. Recently, a group of genes, named “gig” (for Growth in Galleria), have been identified in a contemporary multi-drug resistant clinical isolate of A. baumannii—strain AB5075. Among these so-called gig genes, gigA and gigB were found to promote antibiotic resistance, stress survival, and virulence of AB5075 by interacting with the nitrogen phosphotransferase system (PTSNtr). This study aimed to investigate the roles of gigA/gigB, which appear to comprise a stress-signaling pathway (encoding for an atypical two-component system response regulator and a predicted anti-anti-sigma factor, respectively), and the involvement of ptsP (encoding the Enzyme I component of the PTSNtr) in the growth, stress resistance, and virulence of the widely studied A. baumannii strain ATCC 17978. Genetic analyses of strains harboring mutations of gigA and gigB were performed to investigate the roles of these genes in bacterial growth, stress resistance, evading macrophage defense, and killing of Galleria mellonella larva. In contrast with findings from strain AB5075 where gigA and gigB contribute to aminoglycoside resistance, the data presented herein indicate that the loss of gigA/gigB does not impact antibiotic resistance of strain ATCC 17978. Interestingly, however, we found that deletion of gigA/gigB in the ATCC 17978 background imparts a general growth in laboratory medium and also conferred growth and replication defects within murine macrophages and an inability to kill G. mellonella larvae. Importantly, studies as well as the loss of ptsP restored the phenotypes of the gigA/gigB mutant to that of the wild-type. The data presented herein indicate that in A. baumannii ATCC 17978, the gigA/gigB genes play a key role in both growth and virulence traits, but are dispensable for other stress-resistance survival phenotypes, including aminoglycoside resistance. Our findings thus highlight several similarities and also important differences between the gigA/gigB stress-signaling pathway in two commonly studied isolates of this troublesome pathogen.